AN INVESTIGATION OF CHINESE MIDDLE SCHOOL IN-SERVICE ENGLISH TEACHERS’ ASSESSMENT LITERACY - Lin Dunlai; Su You (University of Kuningan, 2015)
This paper reports an investigation into the status quo of assessment literacy of Chinese middle school in-service English teachers. Using tasks designed by Coombe et al. (2007), the study finds out that Chinese secondary English teachers have low levels of assessment literacy. They are not aware of such principles as authenticity, sensitivity issues about test content and self-assessment. Especially, they are extremely incompetent in understanding statistics about item analysis and distractor efficiency analysis. No significant difference was detected about teachers’ assessment literacy in terms of teaching experience and whether they have taken assessment training courses in any forms. The authors call for a study into language assessment courses offered for secondary English teachers and enough attention paid to the relevance of language assessment training courses to classroom assessment.Keywords: assessment literacy, middle school in-service English teachers. China